STRATEGY FOR ACCELERATING MANAGEMENT AND DEVELOPMENT OF SMEs IN THE KRIYA SUB-SECTOR IN THE CREATIVE INDUSTRY - Aisyah, Risa; Nabhani, Irfan; Aulawi, Hilmi; Hamdani, Nizar Alam (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
The creative industry plays a vital role in economic development, both digitally and conventionally. Indonesia has many industries that are creative and skilled in doing business. The craft business is also diverse. The purpose of this research is to analyze the right strategy for the creative industry of vetiver and bamboo in the Garut Regency. This research was using a qualitative method with a SWOT analysis. In literature studies, a literature review is to understand the theoretical basis for conducting in-depth interviews. Measuring all constructs and research indicators used a research questionnaire distributed in the Craft Industries in Garut Regency. Based on the result, it can be seen that the vetiver and bamboo handicraft industry is in quadrant 2. The recommended strategy given is diversification.